Identification and Characterization of Two Chemotactic Transducers for Inorganic Phosphate in Pseudomonas aeruginosa - Wu, Hong (American Society for Microbiology, 2000)
Two chemotactic transducers for inorganic phosphate (P(i)), designated CtpH and CtpL, have been identified in Pseudomonas aeruginosa. The corresponding genes (ctpH and ctpL) were inactivated by inserting kanamycin and tetracycline resistance gene cassettes into the wild-type genes in the P. aeruginosa PAO1 genome. Computer-assisted capillary assays showed that the ctpH single mutant failed to exhibit P(i) taxis when the concentration of P(i) in the capillary was higher than 5 mM. Conversely, the ctpL single mutant could not respond to P(i) at the concentration of 0.01 mM. The ctpH ctpL double mutant was defective in P(i) taxis at any concentration ranging from 0.01 to 10 mM. To investigate regulation of P(i) taxis, the ctpH and ctpL genes were also disrupted individually in the P. aeruginosa phoU and phoB single mutants. The ctpH phoU and ctpH phoB double mutants were defective in P(i) taxis, regardless of whether the cells were starved for P(i). The ctpL phoU double mutant was constitutive for P(i) taxis, whereas the ctpL phoB double mutant was induced by P(i) limitation for P(i) taxis. The region upstream of ctpL, but not ctpH, contained a putative pho box sequence. Expression of ctpL::lacZ was induced by P(i) limitation in PAO1, while it was constitutive in the phoU mutant. In contrast, the phoB mutant showed only background levels of ctpL::lacZ expression. These results showed that ctpL is involved in the pho regulon genes in P. aeruginosa. The ctpH phoU mutant, which failed to exhibit P(i) taxis, was constitutive for ctpL::lacZ expression, suggesting that the P(i) detection by CtpL requires PhoU. Like PAO1, the phoB and phoU single mutants were constitutive for expression of ctpH::lacZ. Thus, the evidence that the ctpL phoU mutant, but not the ctpL phoB mutant and PAO1, was constitutive for P(i) taxis raised the possibility that PhoU exerts a negative control on P(i) detection by CtpH at the posttranscriptional level.